Evaluation and Medical Management of the Pediatric Patient With Orbital Cellulitis/Abscess: A Systematic Review. Issue 11 (20th October 2021) - Burek, Alina G; Melamed, Svetlana; Liljestrom, Tracey; Qi, Jing; Kelly, Teresa G; Suelzer, Elizabeth; Mitchell, Michelle; Harris, Gerald J; Havens, Peter L
Abstract : BACKGROUND AND OBJECTIVES: Pediatric orbital cellulitis/abscess (OCA) can lead to vision loss, intracranial extension of infection, or cavernous thrombosis if not treated promptly. No widely recognized guidelines exist for the medical management of OCA. The objective of this review was to summarize existing evidence regarding the role of inflammatory markers in distinguishing disease severity and need for surgery; the role of imaging in OCA evaluation; and the microbiology of OCA over the past 2 decades. METHODS: This review was reported in accordance with the Preferred Reporting Items for Systematic Reviews and Meta‐Analyses (PRISMA) guidelines. Searches were performed in MEDLINE (Ovid), Web of Science Core Collection, Scopus, CINAHL (EBSCO), and Cochrane Central Register of Controlled Trials (CENTRAL), most recently on February 9, 2021. RESULTS: A total of 63 studies were included. Most were descriptive and assessed to have poor quality with high risk of bias. The existing publications evaluating inflammatory markers in the diagnosis of OCA have inconsistent results. Computed tomography imaging remains the modality of choice for evaluating orbital infection. The most common organisms recovered from intraoperative cultures are Streptococcus species ( Streptococcus anginosus group, group A Streptococcus, and pneumococcus) and Staphylococcus aureus . Methicillin‐resistant S aureus in culture‐positive cases had a median prevalence of 3% (interquartile range, 0%‐13%). CONCLUSION: This systematic review summarizes existing literature concerning inflammatory markers, imaging, and microbiology for OCA evaluation and management. High‐quality evidence is still needed to define the optimal medical management of OCA.